Thermophilic Composting of Human Feces: Development of Bacterial Community Composition and Antimicrobial Resistance Gene Pool - Werner, Katharina A.; Poehlein, Anja; Schneider, Dominik; El-Said, Khaliel; Wöhrmann, Michael; Linkert, Isabel; Hübner, Tobias; Brüggemann, Nicolas; Prost, Katharina; Daniel, Rolf; Grohmann, Elisabeth (Frontiers in Microbiology, 2022)
In times of climate change, practicing sustainable, climate-resilient and productive agriculture is of primordial importance. Compost from different resources, now treated as wastes, could be one form of sustainable fertilizer creating a resilience of agriculture to the adverse effects of climate change. However, the safety of the produced compost regarding human pathogens, pharmaceuticals and related resistance genes must be considered. We have assessed the effect of thermophilic composting of dry toilet contents, green cuttings, and straw, with and without biochar, on fecal indicators, the bacterial community, and antibiotic resistance genes (ARGs). Mature compost samples were analyzed regarding fecal indicator organisms, revealing low levels of E. coli that are in line with German regulations for fertilizers. However, one finding of Salmonella spp. exceeded the threshold value. Cultivation of bacteria from the mature compost resulted in 200 isolates with 36.5 % of biosafety level 2 (BSL-2) species. The majority is known as opportunistic pathogens that likewise occur in different environments. A quarter of the isolated BSL-2 strains exhibited multiresistance to different classes of antibiotics. Molecular analysis of total DNA before and after composting revealed changes in bacterial community composition and ARGs. 16S rRNA gene amplicon sequencing showed a decline of the two most abundant phyla Proteobacteria (start: 36-48 %, end: 27-30 %) and Firmicutes (start: 13-33 %, end: 12-16 %), whereas the abundance of Chloroflexi, Gemmatimonadetes and Planctomycetes rose. Groups containing many human pathogens decreased during composting, like Pseudomonadales, Bacilli with Bacillus spp., or Staphylococcaceae and Enterococcaceae. Gene-specific PCR showed a decline in the number of detectable ARGs from 15 before to eight after composting. The results reveal the importance of sufficiently high temperatures lasting for a sufficiently long period during the thermophilic phase of composting for reducing Salmonella to levels matching the criteria for fertilizers. However, most severe human pathogens that were targeted by isolation conditions were not detected. Cultivation-independent analyses also indicated a decline in bacterial orders comprising many pathogenic bacteria, as well as a decrease in ARGs. In summary, thermophilic composting could be a promising approach for producing hygienically safe organic fertilizer from ecological sanitation.